Soft robots for healthcare applications : design, modelling, and control - Xie, Shane; Zhang,M; Meng, Wei (The Institution of Engineering and Technology, 2017)
"This book presents novel applications of mechatronics to provide better clinical rehabilitation services and new insights into emerging technologies utilized in soft robots for healthcare, and is essential reading for researchers and students working in these and related fields." - Resumé vydavatele
Keywords: robotika; roboticky asistovaná rehabilitace; zdravotní péče; robotics; robotic assisted rehabilitation; health care; kolektivní monografie; elektronické knihy; collective monographs; electronic books